Did the first Christians worship Jesus? : the New Testament evidence - Dunn, James D. G., 1939-2020. (Louisville, KY : Westminster John Knox Press, 2010)
""Any book by James Dunn is worth reading, and this is no exception. It is a challenging and thought-provoking book that raises central issues for Christian faith and practice."--Christopher Rowland, Dean Ireland Professor of the Exegesis of Holy Scripture, University of Oxford" "This volume offers a transparent and accessible treatment of early Christian monotheistic belief and practice by a scholar who has devoted many years to the study of early Christian convictions about Jesus. Dunn's ability to combine an appreciation for complex issues with clarity of argument make this work a m?ust read' as a riveting introduction to the role and function of Jesus in the worship of God during the first century."--Loren T. Stuckenbruck, Richard Dearborn Professor of New Testament Studies, Princeton Theological Seminary" "In this fascinating exploration of the nascent stages of the Christianity we know today, the author raises some fascinating yet vexing questions: What is worship? Is the fact that worship is offered to God (or a god) what defines him (or her) as "G/god"? What does the act of worship actually involve? The conviction that God exalted Jesus to his right hand obviously is central to Christian recognition of the divine status of Jesus. But what did that mean for the first Christians as they sought to reconcile God's status and that of the human Jesus?" "The questions are challenging but readers are ably guided by James Dunn, one of the world's top New Testament scholars."--BOOK JACKET.
The language of worship -- The practice of worship -- Monotheism, heavenly mediators, and divine agents -- The Lord Jesus Christ.
Includes bibliographical references (p. 152-158) and indexes.
Keywords: Jesus Christ -- Cult -- History; Worship in the Bible; Jesus Christ -- Divinity -- History of doctrines -- Early church, ca. 30-600.; Bible -- Theology